2009
DOI: 10.1055/s-0028-1111105
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Chemical Ototoxicity by Noise

Abstract: High-intensity and/or prolonged exposure to noise causes temporary or permanent threshold shifts in auditory perception. Occupational exposure to solvents or administration of clinically important drugs, such as aminoglycoside antibiotics and cisplatin, also can induce permanent hearing loss. The mechanisms by which these ototoxic insults cause auditory dysfunction are still being unraveled, yet they share common sequelae, particularly generation of reactive oxygen species, that ultimately lead to hearing loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 53 publications
(76 reference statements)
1
14
2
Order By: Relevance
“…Moreover, simultaneous exposure to lead enhanced the noise-induced hearing loss, suggesting an additive effect. This is consistent with other reports which indicated that chronic exposure to low levels of lead may be a risk factor for acquired hearing loss from complex exposures (Hwang et al, 2009; Park et al, 2010; Wu et al, 2000) and simultaneous exposure to ototoxicants that induce oxidative stress may have an additive or synergistic effect (Boettcher et al, 1987; Steyger, 2009). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, simultaneous exposure to lead enhanced the noise-induced hearing loss, suggesting an additive effect. This is consistent with other reports which indicated that chronic exposure to low levels of lead may be a risk factor for acquired hearing loss from complex exposures (Hwang et al, 2009; Park et al, 2010; Wu et al, 2000) and simultaneous exposure to ototoxicants that induce oxidative stress may have an additive or synergistic effect (Boettcher et al, 1987; Steyger, 2009). …”
Section: Discussionsupporting
confidence: 93%
“…For example, simultaneous exposure to even low levels of ototoxic drugs such as cisplatin and noise caused a greater shift in hearing thresholds and histological damage than that caused by isolated exposures (Boettcher et al, 1987). Similarly, simultaneous exposure to organic solvents and noise potentiated the noise-induced permanent threshold shifts (Steyger, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Again, IRSST's assessment seems to be rather conservative and refers to selected agents exclusively. There is further evidence, for instance, that a broad range of volatile lipophilic solvents can exacerbate noiseinduced hearing impairment to a certain extent (4,11).…”
Section: Discussionmentioning
confidence: 99%
“…While causality between the exposure to chemotherapy and the delayed ototoxicity post noise exposure cannot be guaranteed, our service has encountered other patients post platinum-based chemotherapy that developed hearing loss following noise exposure. The synergistic effects between ototoxic compounds and noise on hearing loss have also been demonstrated in animal models, and there is evidence of a common pathway (involving oxidative stress) between noise-induced and platinum-induced ototoxicity [15,16]. The hearing loss and tinnitus experienced by this patient and its subsequent recovery could be described as temporary threshold shift (TTS).…”
Section: Discussionmentioning
confidence: 95%